Analysis of vulnerability and capability for development of supply chain resilience framework - M. Syahri Nur Afif; Sumarsono Sudarto; M. Ibrahim Ats Tsauri; Hery Sumardiyanto (Journal Industrial Servicess, 2022)
The current COVID-19 pandemic has significantly impacted all sectors, including the automotive industry. The automotive industry is one of the industries that contribute significantly to economic growth in Indonesia. With supply chain disruptions and vulnerabilities amid the COVID-19 pandemic, the demand for supply chain resilience is echoing in the business world. It is essential to develop resilience capabilities promptly because supply chain vulnerabilities can cause severe financial loss for organizations. This research aims to group the variables of vulnerability and capability to perform processing more easily in prioritizing the appropriate vulnerabilities and capabilities. The factor analysis method is designed to group variables in many factors with almost the exact nature and characteristics, making it easier to simplify and analyze further. The results of the study found that the vulnerability variable has three factors, namely (i) financial vulnerability, (ii) operational vulnerability, and (iii) external vulnerability, then these three factors are divided into thirteen indicators. While the factors that are formed from the ability variable are five factors, namely (i) cooperation, (ii) anticipation, (iii) financial strength, (iv) capacity, and (v) flexibility, then the five factors are divided into thirteen indicators. Following the research objectives, grouping and simplifying these priority factors can become a reference for researchers or companies to manage supply chains that are more resilient amid disruptions due to the impact of the COVID-19 pandemic effectively and efficiently.